Farmers Motivation In Goldfish Hatchery Business (Cyprinus carpio) in Tanjung Betung Jorong Rambahan Nagari South Rao Pasaman District of West Sumatra Provinc - Rafikah '; Kusai '; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 4 to 10 June 2013 in the Cape Betung Jorong Rambahan Nagari South Rao Pasaman District of West Sumatra Province. This study armed to: Describe the characteristics of fish seed growers, measure bussines motivation level of fish seed and Analyze relationship between several characteristics of seed growers with business motivation of fish seed growers. The method used in this study was a survey method, a total of 12 respondents.Farmers characteristics include: age, education, income, number of dependents and bussiness experience. The level of overall motivation of fish was in medium category with a score of 1.246 means bussiness the motivation to do the business of fish farmers was still dependent on the circumstances and existing capabilities. To analyze the relationship between the characteristics and farmers motivation used the Spearman rank correlation coefficient. Results of this study declare relationship with the motivation that is related to age and not being significant, the relationship between motivation and dependents have weak and not significant relationship, the relationship between motivation and education have a very weak (nonsignificant), the experience of trying to have a weak link and not and income have a significant relationship was not significant and the motivation.Keyword: Motivation, cultivators fish in the pond, Cyprinus carpio